PENGEMBANGAN GAME EDUKASI PETUALANGAN SI WUNDA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KOMPUTASIONAL (COMPUTATIONAL THINKING) SISWA KELAS IV SD - Ahmad Irfan; Gusti Yarmi; Sendi Ramdhani (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
Computational thinking is an essential 21st-century skill that remains low among elementary school students, particularly in Science and Social Studies (IPAS) learning on the topic of changes in the state of matter. This study aims to develop and evaluate the feasibility, practicality, and effectiveness of an educational game entitled The Adventure of Wunda as an interactive learning medium. The research employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The instruments included expert validation sheets, student response questionnaires, and pre-test and post-test assessments of computational thinking skills. The results showed that the game was valid according to experts, received “practical–very practical” responses from students, and effectively improved computational thinking skills, as indicated by a high N-Gain score and a significant difference based on the Wilcoxon test. Therefore, The Adventure of Wunda is feasible and effective for IPAS learning in elementary schools.